Perancangan Ulang Desain UI/UX Aplikasi I-Nusaplant Dengan Metode Design Thinking dan A/B Testing - Saputra, M Ari; Khaira, Ulfa; Saputra, Edi (Politeknik Harapan Bersama, 2025)
I-Nusaplant is a mobile-based application that can detect types of medicinal plants. The I-Nusaplant application was designed by Information Systems students using Android-based leaf images. This application aims to help the community in detecting medicinal plants. The ease of detecting medicinal plants using the application must also be supported by a good appearance and user experience. I-Nusaplant has 3 menus in it, namely Home, Detection, and About. The I-Nusaplant application has shortcomings after conducting interviews with medicinal plant experts, medicinal plant enthusiasts, and general users. The majority of respondents chose the I-Nusaplant application to be redesigned for several reasons related to user experience in running the application. Ease of obtaining information, time to move around each menu, and some features that users need. In doing a redesign, it is necessary to have an in-depth design using UI/UX. The design process in solving problems and generating user needs, researchers use the Design Thinking method to generate ideas to solve user problems. At the analysis stage, problem analysis is carried out, finding solutions to user problems, analyzing user needs. In the design stage, UI/UX design is produced, namely architecture information, user flow, and interface design. UI/UX design will be tested using the Maze tool. After that, compare the results of the old and new I-Nusaplant interface designs using the A/B Testing method. This method aims to see the performance of the old and new application designs. Our A/B testing revealed that the new design, while more complex, is just as efficient as the old one, both scoring 99 this shows that the new design is easy to use by users despite its different design.